The Contribution of the Indonesian Delegation in the Development of Management and Marketing at the BIFF 2022 in South Korea - Guruh Marhaenis Handoko Putro; Erna Nur Faizah; Suryani Yuli Astuti; Ninik Mas’adah (TGO Journal of Community Development, 2026)
The global film industry faces major challenges in terms of management and marketing, which affects the competitiveness of films from various countries, including Indonesia. This community service activity aims to increase understanding of film management and marketing through the participation of the Indonesian delegation in the Busan International Film Festival 2022, which took place on October 8-15, 2022 in Busan, South Korea. The research method used is a qualitative approach with case studies, where data is obtained through direct observation, interviews, and discussions in seminars organized by BIFF. The analysis was carried out with a descriptive approach to describe the role of the Indonesian delegation in presenting managerial strategies and film marketing at the international level. The results of this activity show that the Indonesian delegation has succeeded in making a significant contribution in increasing understanding the importance of effective financial management and appropriate marketing to strengthen the competitiveness of Indonesian films in the global market. In conclusion, this activity not only provides benefits for the development of the national film industry but also strengthens international collaboration in the field of film management and marketing.